Analysis of The Influence of Online Marketing Strategies on Purchase Decisions in The Fashion Industry - Imel Sofy Ariyani; Aflit Nuryulia Praswati (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examine the influence of influencer marketing and customer attitudes toward product on impulse buying behavior in Indonesia's fashion industry, as well as the moderating role of wishful identification . Using a quantitative aproach, data were collected from 165 respondent from aged 18-35 years (including generation Z) through an online questionnaire and anlayzed using Structual Equation Model with Partial Least Squares (SEM-PLS). The findings indicate that influencer marketing significanly affect both attitudes toward product and impulse buying. Additionally, attitude toward product positively influence impulse buying, confirming that emotional and cognitive evaluation play a crucial role in spontaneous purchasing behaviour. However, wishful identification does not significantly influence moderate that purchase impulse are driven more by influencer credibility and authenticity than by a aspirational identification. The study cntributes to the understanding of digital consumers psycology an offers practical insight for marketers in optimizing influencer collaboration and social media engagement strategies.